Tp-Te Interval and Tp-Te/QT Ratio Are Valuable Tools in Predicting Poor Outcome in Sepsis Patients - Li, Duo; Weng, Yibing; Zhen, Genshen; Jiang, Li (Frontiers in Cardiovascular Medicine, 2022)
ABSTRACT Objective About 50% of patients with sepsis have different degrees of myocardial inhibition, known as sepsis-induced myocardial dysfunction（SMD）,which increases the mortality rate of sepsis. Tp-Te interval and Tp-Te/QT ratio reflect ventricular transmural dispersion repolarization (TDR)，and have good predictive value for death in patients with heart disease. This study aimed to investigate the prognostic value of Tp-Te and Tp-Te/QT in patients with sepsis. Methods The current study included a total of 625 participants: 201 sepsis patients, 213 heart failure patients, and 211 healthy participants. According to the severity and outcome，sepsis patients were divided into sepsis group and septic shock group，death group and survival group，to explore the differences of indicators among subgroups of sepsis. The ROC curve was used to analyze the predictive value of the indicators for sepsis patients’ deaths and calculate the cutoff point. Then we investigated the incidence of arrhythmia in sepsis patients with different TDR. The correlation between Tp-Te/QT and the commonly used predictive indicators in ICU was also discussed. Results (1) Tp-Te and Tp-Te / QT in patients with sepsis and heart failure(HF) were significantly higher than the control group (P < 0.01). (2) Compared with sepsis patients, the increase of Tp-Te and Tp-Te / QT is more prominent in HF patients. Especially, the increase of the Tp-Te / QT was statistically significant (P < 0.001). (3) compared with sepsis (no shock) patients,the Tp-Te,Tp-Te/QT and SOFA were increased in septic shock patients（p<0.05）.(4) In the death group, Tp-Te /QT, SOFA, and Apache-II were higher, LVEF was lower than the survival group (P <0.05). (5) ROC curves showed that Tp-Te/QT, SOFA, and LVEF have predictive values for death(p<0.05;AUC=0.808, 0.716, 0.412).The cutoff point of Tp-Te/QT was 0.32.(6)The incidence of arrhythmia is different in sepsis patients with different TDR. (7)There is a significant correlation between Tp-Te /QT and SOFA (p<0.01, r=0.79). Conclusion TDR in sepsis patients is significantly increased,which was between normal and HF patients. Tp-Te and Tp-Te / QT are effective indicators to reflect the severity and poor outcome of sepsis patients.